Scheduling of networked control systems. - Walsh, G.C (IEEE Control systems magazine)
The defining characteristic of a networked control system (NCS) is having one or more control loops closed via a serial communication channel. Typically, when the words networking and control are used together, the focus is on the control of networks, but in this article our intent is nearly inverse, not control of networks but control through networks. NCS design objectives revolve around the performance and stability of a target physical device rather than of the network. The problem of stabilizing queue lengths, for example, is of secondary importance. Integrating computer networks into control systems to replace the traditional point-to-point wiring has enormous advantages, including lower cost, reduced weight and power, simpler installation and maintenance, and higher reliability. In this article, in addition to introducing networked control systems, we demonstrate how dispensing with queues and dynamically scheduling control traffic improves closed-loop performance